Erosión hídrica superficial en campos abancalados del sistema ibérico riojano (valles del Leza-Jubera) - Arnáez Vadillo, José; Ortigosa Izquierdo, Luis María; Oserín Elorza, Marco (Geographicalia, 2017)
In this paper the authors study the erosion processes due to surface water impact in abandoned agricultural terraces ("bancales") of Leza and Jubera valleys (Iberian System). After analysing a sample of 53 plots, two well differentiated groups can be distinguished. The first group (56% of the cases) does not show the effects of overland flow (null erosion); the second group (43 % of the cases) has suffered either mild or severe sheetwash erosion. The vegetal cover is the most important control. Its density and its growth discriminate the erosion in the different types and sectors of slope.
Keywords: Erosion; sheetwash erosion; abandoned agricultural terraces; Iberian System.